GENDER-SOCIAL FEATURES OF PROFESSIONAL MALADJUSTMENT OF A DOCTOR - Потеряева, Елена Леонидовна; Федорова, Лилия Темурхановна; Смирнова, Елена Леонидовна; Несина, Ирина Алексеевна (Medicine in Kuzbass, 2025)
More than 668 thousand doctors and more than 1650 thousand paramedical workers are employed in the healthcare sector of the Russian Federation. Among them, the share of female doctors is about 70%. Medical activity is associated with a great emotional burden in terms of responsibility (moral, administrative and legal) for every decision made to the patient and his relatives, the administration and the work team. For this reason, it is relevant to study the influence of gender, marital status and the presence of children on resistance to professional stress in the work of a doctor. The study aims to the influence of gender, marital status and the presence of pupils in the family on the peculiarities of professional maladjustment of a doctor. Materials and methods. A survey of 346 doctors was conducted. The following were studied: cognitive behavioral assessment according to the questionnaire of authors O.M. Rodina, M.A. Dmitrieva «Assessment of professional maladjustment», the questionnaire of authors N.E. Vodopyanova, E.S. Starchenkova, A.D. Nasledov «Professional burnout», a four-dimensional questionnaire for assessing distress, depression, anxiety and somatization (4DSQ). Results. It was found that gender psycho-physiological characteristics of female doctors can be traced even with a low degree of professional maladjustment. Women with a low degree of professional maladaptation, compared with male doctors, have significantly higher emotional burnout, depersonalization, reduction, and the integral indicator of professional burnout. With a moderate degree of professional maladjustment, indicators of clinically borderline psycho-vegetative disorders increase sharply and gender differences are erased. No statistically significant influence on the degree of professional disadaptation was found for such social indicators as length of service, marital status, and the number of students in the family. Conclusions. 1. The rate of development of emotional burnout under the influence of occupational stress is significantly higher in women than in men. 2. The reduction of personal achievements undergoes maximum change up to development of professional maladaptation of a moderate degree, which makes it impossible to provide medical care at a high-quality level. 3. With a low level of professional adaptation, there is a higher prevalence of somatization among female doctors, than among men.